Capacity assessment of Liberia for health emergencies and disaster preparedness and response - Mosoka Fallah; Basil Benduri Kaburi; Kofi Mensah Nyarko; Delia Akosua Bandoh; Abraham Nyenswah; Issiaka Sombie; Simon Nyovuura Antara; Virgil Kuassi Lokosso; Ernest Kenu (Journal of Interventional Epidemiology and Public Health)
Introduction: West Africa continues to experience recurrent epidemics of infectious diseases and other public health emergencies. Most of which have resulted in deaths, disabilities and loss of property due to the weak public health system including low capacity to respond, a lack of a preparedness. Liberia, one of the three countries hit by the Ebola epidemic has taken several steps to improve its preparedness and response to public health emergencies. We assessed Liberia's status of public health emergencies preparedness and response and to identify gaps which could prevent her from effectively responding according to IHR core capacities. Methods: We conducted a cross-sectional study which involved desk reviews and interviews with key stakeholders of the health sector in Liberia. Data collection was done in-country from April to July 2018. Findings from both sources were triangulated and described under the IHR core capacity themes. Results: Liberia has a well-organized public health institute and which coordinates and helps with the implementation of the various plans and policies. The country has plans and policies covering some aspects of the international Health regulation (IHR) core capacities developed. The national public health institute implements the plans and policies, and coordinates preparedness and response activities. There is no dedicated budget line for emergency preparedness and response activities. Conclusion: Liberia has made good strides in preparing and responding to public health emergencies. However, the lack of dedicated source of funding serves as a threat to the sustainability of the gains the country has made so far